Deciphering the Role of Integrated Nutrient Management on Saffron Stigma Yield under Climatic Conditions of Quetta Balochistan - Siddiqui, Muhammad Raza; Khan, Jahangir; Shah, Muhammad; Reki, Abdul Razaq; Sadiq, Nadeem; Khetran, Munir Ahmed; Khan, Nanak; Amanullah; Ullah, Noor; Nauman, Mohammad; Ahmed, Syed Riaz (Indus Journal of Bioscience Research, 2025)
Saffron is the most expensive spice grown in arid and semiarid regions of the globe. Integrated nutrient management has a significant impact on saffron growth and quality by improving nutrient mobilization, water hold capacity, and improvement of soil health. To evaluate the impact of organic and inorganic fertilizer on saffron stigma yield a study was conducted at Balochistan Agricultural Research and Development Center, Quetta. The study comprised of six integrated nutrient management treatments including control under randomized complete block design. Farmyard manure alone and in combination with different NP doses and NP doses alone were used to evaluate its impact on saffron yield and floral attributes. Our results showed better flowering under farmyard manure and moderate nitrogen and phosphorous treatments while the flowering delayed under high NP application. Saffron stigma, stamen and petal dry weight data showed higher yield under Farmyard Manure @ 30 tons producing 7.79, 6.93 and 102.6 milligrams of dry weight for single flower. FYM treatment also increased fresh weight of stigma, stamen and petals. FYM with balanced application of nitrogen and phosphorous also revealed positive impact on stigma and floral attributes. The correlation and PCA analysis depicted positive association of stigma with stamen 0.61 and petal dry weight 0.55 which shows that integrated nutrient management can improve saffron yield along with sustainable improvement of soil health.